Ampliando la comprensión de la pobreza energética desde el enfoque de capacidades: hacia una mirada construida desde las personas afectadas - Victoria Pellicer-Sifres (Revista Iberoamericana de Estudios de Desarrollo)
This paper seeks to contribute to a better understanding of fuel poverty, and to include the vision of people who are suffering the problem. To do this, using the capability approach and a qualitative fieldwork, we propose a conceptual framework to rethink and redefine the phenomenon, in order to: i) link the problem with social justice and with vulnerability; ii) broaden the spectrum of causes and link them with personal, social, environmental and structural issues; iii) understand the consequences as the deprivation of a series of capabilities, operations and agency that prevent people from living the life they value. Moving towards this broader understanding is relevant, as the first step to design more effective policies aligned with the perceptions and aspirations of people in fuel poverty.